1983
DOI: 10.1210/endo-113-5-1592
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Relationship of Calcium Ion Channel Antagonists at the Pituitary Gonadotrope*

Abstract: We have compared the potencies of chemically heterogeneous classes of Ca2+ ion channel inhibitors as antagonists of GnRH-stimulated LH release from the rat pituitary. Verapamil and its more potent derivative methoxyverapamil (D600) are effective inhibitors. The 1,4-dihydropyridines, however, had no antagonistic efficacy, and diltiazem had slight inhibitory action, but only when preincubated with cells before GnRH addition. The observation that the potency series of antagonists was identical (verapanoids greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Although nimodipine can block very potently the effects of high K on GH cells, the drug weakly inhibits basal levels of hormone secretion or the effects of stimulatory peptides, like TRH (Conn, Rogers & Seay, 1983;Enyeart et al 1985). Likewise, therapeutic doses of dihydropyridines have little effect on the secretion of prolactin or growth hormone in vivo (Struthers, Millar, Beastall, McIntosh & Reid, 1983;Abadie, Gauville & Brisson, 1984;Isles, Baty & Dow, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Although nimodipine can block very potently the effects of high K on GH cells, the drug weakly inhibits basal levels of hormone secretion or the effects of stimulatory peptides, like TRH (Conn, Rogers & Seay, 1983;Enyeart et al 1985). Likewise, therapeutic doses of dihydropyridines have little effect on the secretion of prolactin or growth hormone in vivo (Struthers, Millar, Beastall, McIntosh & Reid, 1983;Abadie, Gauville & Brisson, 1984;Isles, Baty & Dow, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…LH release has been shown to be partially or completely dependent on Ca2+ influx (2,19). This Ca2+ influx apparently involves L-type channels (19,28), although there is also some disagreement on this point (2,29). However, recent studies, which monitored LH release on a relatively rapid time base, indicated that L-channel blockers did not block an initial spike of LH release but did block subsequent release over an extended time course (19).…”
Section: Methodsmentioning
confidence: 99%
“…Related work also suggested that the mechanism forCa2*-dependent hor mone release of LH by gonadotrophs was mediated by an ion channel chemically distinct from that in smooth muscle [8], where action potentials play a prominent role in media tion of Ca2* entry. Therefore, it is clear that previous work, where GnRH-stimulated release of LH has been measured, is consistent with the view that conventional all-or-none ac tion potentials, as found in mammalian nerve and muscle cells, do not feature prominently in Ca2+ entry leading to gonadotrophin release.…”
Section: Voltage Fluctuations As a Mechanism O F Ca> Entry In Gonadotmentioning
confidence: 99%